Managing Menstrual Cycle Medication During Hajj and Fasting: Juridical Considerations - Pratama, Tommy; Muhammad, Hasman; Syahmirwan, Syahmirwan; Safarsyah, Alfandi (Research Horizon, 2023)
Every type of worship has pillars and conditions for the worship to be considered valid, as is the case with the worship of fasting during Ramadan and the pilgrimage of Hajj. However, the menstrual cycle often becomes an issue for women in performing the Hajj pilgrimage and fasting during Ramadan, as Islamic law prohibits women who are menstruating from engaging in worship. The advancement of knowledge and technology has given rise to a product, namely medications related to the menstrual cycle, medicines to accelerate or delay menstruation. The use of these medications has sparked discussions among Islamic jurists (fuqaha), Muslim scholars, and medical experts, as this issue pertains to the needs of the Muslim community. The absence of clear textual evidence (nash) from the Qur'an and the Sunnah has led to debates among jurists regarding deriving legal rulings on the matter of using medications related to the menstrual cycle. Scholars, in formulating the ruling on the consumption of such medications, base their conclusions on the method of maslahah mursalah (unrestricted public interest).